2021
DOI: 10.1111/soin.12413
|View full text |Cite
|
Sign up to set email alerts
|

Gun Owners and Gun Control: Shared Status, Divergent Opinions

Abstract: After each mass public shooting, an inevitable debate surrounding the tools used to carry out the attack ensues. This debate is marked by two sides: those who endorse controlling access to firearms and those who oppose restrictions to the Second Amendment. Implicit in this dialogue is the assumption that gun owners are a homogenous group who stand in opposition to the gun control legislation. Using a national sample of American gun‐owning adults, we examine gun control attitudes among those who share the gun o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The main finding that emerges from this study is that gun owners differ greatly in terms of their level of engagement in gun-related activities, reasons for owning a firearm, values, and beliefs. Our findings demonstrate support for the position, as a recent wave of studies have showed (Boine et al 2020; Burton, Logan, et al 2021; Burton, Pickett, et al 2021; Celinska 2007; Jouet 2019; Lacombe et al 2019; Losee et al 2021; Mencken and Froese 2019; Warner and Ratcliff 2021; Yamane 2017, Yamane et al 2021), that the gun-owning population is far more complex than that depicted by stereotypes displayed in the media and sometimes found in existing scholarship on gun owners. Another way gun owners differ is the extent to which they adhere to a collective gun owner identity.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The main finding that emerges from this study is that gun owners differ greatly in terms of their level of engagement in gun-related activities, reasons for owning a firearm, values, and beliefs. Our findings demonstrate support for the position, as a recent wave of studies have showed (Boine et al 2020; Burton, Logan, et al 2021; Burton, Pickett, et al 2021; Celinska 2007; Jouet 2019; Lacombe et al 2019; Losee et al 2021; Mencken and Froese 2019; Warner and Ratcliff 2021; Yamane 2017, Yamane et al 2021), that the gun-owning population is far more complex than that depicted by stereotypes displayed in the media and sometimes found in existing scholarship on gun owners. Another way gun owners differ is the extent to which they adhere to a collective gun owner identity.…”
Section: Discussionsupporting
confidence: 85%
“…If gun ownership influences political opinions (Burton, Logan, et al 2021; Joslyn 2020), political affiliation also plays a significant role in terms of whether and how individuals are introduced to gun culture. For instance, going to a college with a higher proportion of Republican students makes it more likely to have access to a shooting sports organization on campus (McElroy and Coley 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to understanding gun attitudes, the form of racial prejudice that is most theoretically germane is racial resentment (Filindra & Kaplan, 2016; O'Brien et al., 2013)—a symbolic form of prejudice that is less explicit than traditional racism and that reflects a merging of anti‐Black affect with denials of discrimination (Kinder & Sanders, 1996; Rabinowitz et al., 2009). As Filindra and Kaplan (2017, p. 417) argued, “the narrative of gun rights as developed since the 1970s reflects a discourse of racial resentment.” Consistent with this argument, a growing number of studies found that racially resentful Americans tend to oppose gun control (Burton, Logan, et al., 2021; Filindra & Kaplan, 2016, 2017; O'Brien et al., 2013; Wetts & Willer, 2019) and tend to own more guns (Filindra et al., 2021; O'Brien et al., 2013). More broadly, two decades of research demonstrated that racial resentment is one of the strongest and most consistent predictors of criminal justice attitudes (Bobo & Johnson, 2004; Brown & Socia, 2017; Drakulich et al., 2020; Enns & Ramirez, 2018; Matsueda & Drakulich, 2009; Pickett & Chiricos, 2012; Simmons, 2017; Unnever & Cullen, 2010).…”
Section: The Political Relevance Of Race and Gunsmentioning
confidence: 94%
“…Unsurprisingly, gun owners hold particular attitudes about gun policy in the United States. In general, they are much more supportive of expanding gun rights than their non-gun owning counterparts (Parker et al 2017), but gun owners are not uniform in their opposition to gun regulation (Burton et al 2021; Siegel et al 2021). Although there are a number of gun regulation policies on which gun owners and non-gun owners agree, there are many on which they strongly disagree, with gun owners generally rejecting gun ownership restrictions (Barry et al 2018; Parker et al 2017).…”
Section: The Impact Of Gun Ownership On Gun Regulation Attitudesmentioning
confidence: 99%